Agrobiodiversity conservation on-farm: Nepal's contribution to a scientific basis for national policy recommendations, 10 February 2002, Kathmandu, Nepal - Gauchan, D.; Sthapit, B.R.; Jarvis, Devra I.; International Plant Genetic Resources Institute (2003)
Nepal's policy-makers are presently faced with implementing a myriad of national and international policy obligations that are relevant to the conservation, use and development of agricultural biodiversity. Rapid changes in the recent international policy scenario, the complexity of the emerging biodiversity policy issues, and the diversity of the stakeholders involved in the agrobiodiversity sector require good information by the policy-makers for the development of realistic policy relevant to the needs and goals of the Nepalese agroeconomy. This proceedings is intended to provide a scientific basis for policy recommendation from information generated from empirical research activities carried out by the Nepal component of the global project ”Strengthening the Scientific Basis of in situ Conservation of Agricultural Biodiversity On-farm”1 over the past 5 years (1997-2002).